HCI evaluation with Cognitive Dimensions of Notations - Ferreira, Juliana Jansen; Segura, Vinícius (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2019: Anais Estendidos do XVIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2019.8375, 2019)
During the design and development of a technological artifact or when such artifact is already in the hands of users, an inspection method can help researchers and practitioners deal with not only usability issues, but also provide a common language to evaluate different design alternatives. The Cognitive Dimensions of Notations framework (CDNf) is a methodological resource designed to identify and discuss cognitive loads imposed by notations. In this six hour short course, we aim to talk about our experience with CDNf alone and combined with other HCI methods and to explore CDNf in practice with hands on activities to show participants how it can be a useful resource.